Enumerating Problems Concerning Endomorphisms of Double Vertex Wheel Graphs - Yu Li; Hailong Hou; Kaidi Xu (Journal of Mathematics)
We can define six classes of endomorphisms on a graph, and they always form a chain based on set inclusion. The concepts of endomorphism type and endomorphism spectrum were introduced by Böttcher and Knauer in 1992. They provided a systematic and organized approach to study endomorphisms of graphs. In this paper, we focus on the double vertex wheel graphs and provide a detailed description of their endomorphism spectra and endomorphism types.